INVENTARISASI TANAMAN PEKARANGAN DAN PEMANFAATANNYA SEBAGAI BAHAN PANGAN OLEH MASYARAKAT TANJUNGAN, DI KABUPATEN TANGGAMUS, LAMPUNG - Wakhidah, Anisatu Z.; Silalahi, Marina (Universitas Tanjungpura, 2020)
The diversity of homegardens plants in the tropics region is very high. Therefore, homegarden can be a conservation site for local species. In addition, homegarden plays an important role in providing food resources for rural communities, especially for farmers. The community at Tanjungan Village is one of the communities in Lampung that almost entirely work as farmers. Ethnobotanical studies of the community are still rarely carried out, therefore this research was conducted. The purpose of this study is to explain the composition of homegarden plants in Tanjungan Village. Secondly to explain the diversity of homegarden plant species used as daily food. The third to describe a source of homegarden plants acquisition at Tanjungan Village. Research data were collected using participant observation interview methods and questionnaires, then the data were analyzed using qualitative approach. The results showed that as many as 155 species, 15 cultivars, and 5 variants belonging to 58 families compiled the diversity of homegarden plants at Tanjungan Village. Recorded as many as 13 use categories of homegarden plants which food is the highest category of species (66 species and 11 cultivars 34 families). Fabaceae is the family with the highest number of food species (6 sp.). The most commonly found food plants are gedang (Carica papaya) with the frequency of discovery 27 times. The source of the acquisition of the seeds of the garden plants in Pekon Tanjungan, namely the collection from neighbors, seeds from the garden, spontaneous growing seeds, sellers of plant seeds, and the distribution of seedlings from the local agricultural service.AbstrakKeanekaragaman tanaman pekarangan di wilayah tropis sangat tinggi sehingga pekarangan dapat menjadi situs konservasi bagi spesies lokal. Selain itu, pekarangan memainkan peran penting dalam menyediakan sumber makanan untuk masyarakat pedesaan, terutama bagi para petani. Masyarakat Pekon Tanjungan, di Kabupaten Tanggamus, Lampung hampir seluruhnya bekerja sebagai petani. Sejauh ini, studi etnobotani pada pekarangan masyarakat tersebut masih jarang ditemukan. Oleh karena itu dilakukan penelitian ini dengan tujuan, pertama menginventarisasi spesies dan komposisi tanaman pekarangan di Pekon Tanjungan. Kedua, menganalisis spesies tanaman pekarangan yang digunakan sebagai bahan pangan. Ketiga, mengetahui sumber perolehan tanaman pekarangan di Pekon Tanjungan. Data penelitian dikumpulkan dengan menggunakan metode wawancara observasi partisipan dan kuesioner, kemudian data dianalisis menggunakan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa 155 spesies, 15 kultivar, dan 5 varian yang tergolong dalam 58 famili tumbuhan menyusun keanekaragaman tanaman pekarangan di Desa Tanjungan. Tercatat sebanyak 13 kategori penggunaan tanaman pekarangan. Bahan pangan merupakan kategori guna dengan jumlah spesies tertinggi (66 spesies dan 11 kultivar 34 famili). Sebagian besar spesies tersebut berasal dari suku Fabaceae yakni sebanyak 6 spesies. Tanaman pangan yang paling banyak ditemukan adalah gedang (Carica papaya) dengan frekuensi penemuan 27 kali. Sumber perolehan bibit tanaman pekaraga di Pekon Tanjungan, yaitu tetangga, kebun, benih tumbuh spontan, penjual bibit tanaman, dan dinas pertanian setempat.Kata Kunci: etnobotani pekarangan, sumber bahan pangan, komposisi tanaman pekarangan, pekon tanjungan